The Transformational Leadership Design of Vice-Chancellors/Rectors and Human Resource Management in Public and Private Higher Institutions of Learning in Southeast Nigeria - Dimokpala, Chukwudi Ikenna Christopher (Advances in Social Sciences Research Journal, 2025)
The research focuses on the transformational leadership design of Vice-Chancellors/Rectors and Human Resource Management. It aims to investigate how this design has been utilized in private and public higher learning institutions in Southeastern Nigeria. Four research questions and a null hypothesis guided the study. Thus, the four questions concern the leadership design adopted by Vice-Chancellors/Rectors in human resource management, specifically in staff development, motivation, and discipline. Furthermore, a review of the literature on leadership, transformational leadership design, and human resource management was conducted. This is followed by a theoretical framework, which includes the theory of human relations, emphasizing that individuals are more motivated to participate actively in achieving organizational goals when treated as human beings. Herzberg’s theory of motivation identified two key factors: hygiene factors, which include salary and working conditions, and motivator factors, which encompass opportunities for development, responsibilities, and appreciation. For him, these two factors must coexist for a good result. Maslow's hierarchy of needs theory states that the individual's basic physiological needs are at the pyramid's base. When these needs are fulfilled, people move on to their safety needs, social well-being, self-esteem, and, finally, their need for self-actualization. Finally, the contingency theory of leadership maintains that there is no one best way to organize. An organization's structure is influenced by the environment in which it operates. The design utilized for the research is descriptive. Vice-Chancellors/Rectors and Educators in both private and public Higher Institutions of Learning in South-East Nigeria comprised the total population of the study. The sample for the research consisted of 34 Vice-Chancellors/Rectors and 21,575 Educators from 34 higher institutions of Learning in 72 local government areas across five states in South-East Nigeria. The questionnaire consists of 53 items, titled "Transformational Leadership Design of Vice-Chancellors/Rectors and Human Resource Management.” The mean and standard deviation were employed to answer the research questions, whereas four hypotheses were tested using the chi-square test at a 0.05 (5%) significance level.